Implementasi Media Stik Es Krim Berbasis Coding dalam Pengenalan Bilangan pada Anak Usia Dini - Siti Rofi'ah; Latifatus Sa'adah; Helina Himmatul Ulya Lina (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
This study aims to describe the implementation of ice-cream stick media using a coding technique and to analyze its contribution to improving children's numerical recognition skills. The research employed a descriptive qualitative approach with subjects consisting of Group A children aged 4–5 years, along with two classroom teachers as informants. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The findings indicate that the use of ice-cream sticks supports children in recognizing and sequencing numbers more accurately. Children were also able to classify and arrange the sticks according to the numbers provided, enabling a more concrete understanding of quantity concepts. The learning activities were enjoyable, fostering motivation and enhancing children's self-confidence. The implications of this study affirm that ice-cream stick media with a coding technique is effective as an early numeracy teaching aid because it is easy to apply, inexpensive, and aligns well with the learning characteristics of young children.